(untitled) (Research, Society and Development, 2020)
Introduction: Chronic conditions strongly impact the quality of life of children who experience them. Specific relationships and responsibilities can, as a result, change the quality of life of healthy siblings living in the same family. Objective: To identify the coping adopted by healthy siblings in view of the family context involved in chronic care and to highlight the nurse for the care of their needs. Methodology: This is an Integrative Literature Review. 810 publications were identified through the Virtual Health Library. When considering the filters article, thesis, available text, all languages and time frame from 2002-2020, 394 works emerged. After discarding repeated articles, with restricted access or that did not apply to the scope and reading the titles, abstracts and content, 15 articles were selected. Results: Discovering the Chronic Condition is an impacting experience. Several responsibilities and feelings are touched on in the parents. The healthy child’s relationship with parents and siblings shows significant changes, since there is a centrality of chronic care. For these families, greater professional support is essential. Final considerations: For healthy siblings, the presence of parents is reduced. In general, healthy siblings relate well to those who have some commitment, but face an overload of responsibilities, demands for success and maturity. The lack of affection is significant and compromises its development. Therefore, school, personal and social performances perceive these influences. Nurses have an important role in these settings. Family-centered care should include healthy siblings in the therapeutic process.